Gender, Language and Politics: the Representation of Theresa May on Twitter - Umi Zakiyah; Ribut Wahyudi (Journal of Language and Literature, 2022)
The relationship between women leaders’ language, social media, and politics has been interesting to be discussed.  However, there are lacks previous studies that examined the women leaders’ language and how the word choices represent women leaders on Twitter.Thus, this study aims to find out Theresa May’s language on Twitter and how those word choices represent herself as a woman leader. The data are taken from the tweets on Theresa May’s Twitter account over the last six months of her leadership reign (from January until July 2019), which focused on her crucial tweets about politics and leadership. The researchers adopted four theories to capture and analyze the data from different angles to produce the rich analysis of Theresa May’s word choices and representation on Twitter. The study revealed several word choices used by Theresa May into four categories: (1) announcement tweets, (2) attack/negative tweets, (3) personal characteristics, and (4) policy. Furthermore, the study also found that Theresa May utilized those word choices to represent herself as a political leader. She also used metaphors and pronouns to shape the desired representation. Furthermore, not all PDA elements by Fairclough Fairclough (2012) were employed due to the limited characters number on Twitter or other possible purpose(s). This study is beneficial to enrich the knowledge on how the use of language by woman leader is implicated within social and political contexts of a country. The Linguistics analysis on gender, language, and politics is another take away from this research.